Spontaneous Enantiomorphism in Poly-phased Alkaline Salts of tris(oxalato)ferrate(III): Crystal Structure of Cubic NaRb5[Fe(C2O4)3]2 - Piro, Oscar Enrique (2018)
We show here that the phenomenon of spontaneous resolution of enantiomers occurs during the crystallization of the sodium and rubidium double salts of the transition metal complex tris(oxalato)ferrate(III), namely sodium penta-rubidium bis[tris(oxalate) ferrate (III)], NaRb5[Fe(C2O4)3]2. One enantiomer of the salt crystallizes in the cubic space group P4332 with Z = 4 and a Flack absolute structure parameter x = -0.01(1) and its chiral counterpart in the space group P4132 with x = -0.00(1). All metal ions are at crystallographic special positions: the Fe(III) ion is on a threefold axis, coordinated by three oxalate dianions in a propeller-like conformation. One of the two independent Rb(I) ions is on a twofold axis in an eightfold coordination with neighboring oxalate oxygen atoms, and the other one on a threefold axis in a sixfold RbO6 coordination. The sodium ion is at a site of D3 point group symmetry in a trigonal-antiprismatic NaO6 coordination.